The relationship between lower-body force-time variables and skating performance in female ice hockey players - Geneau, M. C.; Tsai, M.-C.; Agar-Newman, D.; Geneau, D. J.; Klimstra, M.; James, L. P. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Ice hockey is a team invasion sport characterized by repeated high-intensity skating efforts, technical and tactical skill, physical contact, and collisions requiring considerable levels of muscular strength. The purpose of this study was to evaluate the relationships between lower-body vertical force-time metrics and skating qualities in subelite female ice hockey players.